Ismaili Sources, Studies, History and Traditions - Daftary, Farhad (Middle East and Islamic Studies E-Books Online, Collection 2025., 2026)
Until recently, Ismailis were studied and evaluated almost exclusively on the basis of evidence often fabricated by adversaries. Thus, a variety of legends and misrepresentations circulated in Europe as well as among other Muslim communities regarding the teachings and practices of this Shiʿi Muslim community. With the access of modern scholars to numerous Ismaili manuscript sources, preserved in Yemen, Syria, Iran, Central Asia and India, a completely new image of the Ismailis has emerged. A leading authority in Ismaili studies, Farhad Daftary draws on the results of modern scholarship in the studies collected here on Ismaili history and aspects of Ismaili thought and traditions.